Design of stick-framed wood roofs under tornado wind loads - Bain, Caspar L. D.; Kopp , Gregory A.; El Ansary , Ayman M. (Frontiers in Built Environment, 2022)
Light-frame wood construction comprises nearly 90% of the housing industry in Canada and the United States. The roofs of these houses can be constructed either entirely on site or using prefabricated trusses. Assembling the roof structure on site, otherwise known as stick-framing, is a framing technique with current code guidelines that are based on past practice and limited consideration of wind loads. This makes these roof structures susceptible to failure in high-speed wind events, such as tornadoes. This research proposes improved stick-framing guidelines that would work for EF-2 tornadoes. Using non-linear finite element analysis, a stick-framed roof was designed following the guidelines in the National Building Code of Canada. Non-linear links were used to model all of the connections between the members in the roof structure, with frame elements used to represent the members. Increasing wind loads were applied to the structure and the first elements of the roof that failed were improved using an iterative performance-based design approach until the performance target of resistance to EF-2 tornadoes was achieved. The failure of the roof-to-wall-connections and the lack of members used in the framing were the two main issues highlighted and addressed. Damage survey photos were used to compare failures observed in the model with failures after real tornado events, which demonstrate many similar failure modes. The research recommends the requirements to ensure stick-framed roofs can withstand EF-2 tornadoes. Most notable is an improved gable end frame, which gives the structure more roof-to-wall connections, as well as a more structurally sound frame where the loads are the highest. Other additions include struts, hurricane ties at all roof-to-wall connection locations and increased number of nails in various connections throughout the repeating inner frames. Minimum member sizes and qualities for each type of member used in the roof structure are also recommended.